Isolated Distal Deep Vein Thrombosis: Perspectives from the GARFIELD-VTE Registry - Schellong, Sebastian M.; Goldhaber, Samuel Z.; Weitz, Jeffrey I.; Ageno, Walter; Bounameaux, Henri; Turpie, Alexander G. G.; Angchaisuksiri, Pantep; Haas, Sylvia; Goto, Shinya; Zaghdoun, Audrey; Farjat, Alfredo; Nielsen, Joern Dalsgaard; Kayani, Gloria; Mantovani, Lorenzo G.; Prandoni, Paolo; Kakkar, Ajay K. (Thrombosis and Haemostasis, 2019)
Isolated distal deep vein thrombosis (IDDVT) represents up to half of all lower limb DVT. This study investigated treatment patterns and outcomes in 2,145 patients with IDDVT in comparison with those with proximal DVT (PDVT; n = 3,846) and pulmonary embolism (PE; n = 4,097) enrolled in the GARFIELD-VTE registry. IDDVT patients were more likely to have recently undergone surgery (14.6%) or experienced leg trauma (13.2%) than PDVT patients (11.0 and 8.7%, respectively) and PE patients (12.7 and 4.5%, respectively). Compared with IDDVT, patients with PDVT or PE were more likely to have active cancer (7.2% vs. 9.9% and 10.3%). However, influence of provoking factors on risk of recurrence in IDDVT remains controversial. Nearly all patients (IDDVT, PDVT, and PE) were given anticoagulant therapy. In IDDVT, PDVT, and PE groups the proportion of patients receiving anticoagulant therapy was 61.4, 73.9, and 81.1% at 6 months and 45.8, 54.7, and 61.9% at 12 months. Over 12 months, the incidence of all-cause mortality, cancer, and recurrence was significantly lower in IDDVT patients than PDVT patients (hazard ratio [HR], 0.61 [95% confidence interval [CI], 0.48–0.77]; sub-HR [sHR], 0.60 [95% CI, 0.39–0.93]; and sHR, 0.76 [95% CI, 0.60–0.97]). Likewise, risk of death and incident cancer was significantly (both p < 0.05) lower in patients with IDDVT compared with PE. This study reveals a global trend that most IDDVT patients as well as those with PDVT and PE are given anticoagulant therapy, in many cases for at least 12 months.
Keywords: deep vein thrombosis; isolated distal deep vein thrombosis; 12-month observational study; GARFIELD-VTE registry